The Effectiveness of Writing Journal and Feedback on Increasing Writing Proficiency at University Students - Farikha, Ninik (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2020)
The practice of giving feedback in teaching and learning process seems to be unclear. Unclear is an inconsistent feedback given by the teacher during teaching learning process. Teacher rarely gave the evaluation because giving feedback will be time-consuming. Teacher used studentsâ€Ÿ task sheet instantly. Teachers need to check the studentsâ€Ÿ work and give the feedback to studentsâ€Ÿ task. This way makes students aware that something â€œwrongâ€ appears and they need to consider it to their improvement. This study intends to investigate the difference between studentsâ€Ÿ achievement in writing proficiency who are taught by using writing journal technique and given feedback and those who are not. The research design used in this research was quasi experimental design. Experimental design is the conceptual outline in doing experiment. In this experimental design, the researcher used two English Program classes of IAIN Kediri. First class was experimental class which is treated using writing journal and giving feedback while the second class was control class which is not treated using writing journal and giving feedback. The results revealed that using writing journal technique in learning was effective to increase the studentsâ€Ÿ writing ability. It was good technique to improve studentsâ€Ÿ ability in writing proficiency.